Chemico-biological sewage treatment plants for PE< 9.999 = Chemiczno-biologiczne oczyszczalnie ścieków dla RLM < 9 999 - Heindrich, Zbigniew; Stańko, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Removal of nitrogen and phosphorus compounds is not required in the case of sewage treatment plants serving the settlement units of up to 9.999 citizens and not charging treated sewage into staying waters. Therefore, it is possible to reduce the range of water treatment to merely two requirements: the BOD_5 and the concentration of suspended solids.
Keywords: ścieki; oczyszczanie ścieków; oczyszczalnia chemiczno-biologiczna; chemico-biological sewage treatment plants; nitrogen and phosphorus compounds